Legacies, inheritances and ruptures in Haitian literature written by women - Rebolledo Garrido, Edith Aurora (2022)
In this work, we propose an analysis of a fraction of Haitian literature written by women, which focuses particularly on three contemporary narrative works that address state violence during the Duvalierist regime and its material and symbolic effects on Haitian families inside and outside the country. Serving from the concept of “home”, understood as the material and symbolic space for all kinship relationships, literary works by three Haitian women writers, Edwidge Danticat, Emmelie Prophète and Évelyne Trouillot, will be analyzed. Likewise, we will look at how in these literary works parents transfer towards their offspring traditions assimilated by themselves, and which they have incorporated into their everyday lives.